Effects of strontium addition and T6 heat treatment on uniaxial fatigue of A356 aluminum alloy: Fatigue life and cyclic behavior - Haskel T.* (2022)
© 2022 John Wiley & Sons Ltd.The effects of strontium addition and T6 heat treatment on fatigue behavior of A356 aluminum alloy were studied in this paper. Uniaxial fatigue tests were carried out by using constant stress amplitude. In addition, microstructural analysis of porosity and fracture surface were performed on the material. Results showed that the alloy at T6 conditions presented the best fatigue life, mainly in low cycle fatigue. In high cycle fatigue, the fatigue life of as-cast and heat treatment alloys almost converged to the same alternating stress. The strontium modified alloys presented higher porosity levels than unmodified ones, which reduced the fatigue life. The stress–strain hysteresis loops showed that the A356 + T6 alloy reached the highest total strain ranges and that depending on the stress level applied, the alloy may or not present cyclic hardening. The fracture analysis revealed porosity near the surface was the main fatigue failure nucleation site for strontium modified alloys.